Ticks and rickettsiae from wildlife in Belize, Central America. Issue 1 (December 2016) - Lopes, Marcos; Junior, Joares; Foster, Rebecca; Harmsen, Bart; Sanchez, Emma; Martins, Thiago; Quigley, Howard; Marcili, Arlei; Labruna, Marcelo
Abstract Background The agents of spotted fevers in Latin America areRickettsia rickettsii, R. parkeri, Rickettsia sp. strain Atlantic rainforest, andR. massiliae . In Continental Central America, R. rickettsii remains the only known pathogenic tick-borne rickettsia. In the present study, ticks were collected from wild mammals in natural areas of Belize. Besides providing new data of ticks from Belize, we investigated rickettsial infection in some of these ticks. Our results provide ticks harboring rickettsial agents for the first time in Central America. Methods Between 2010 and 2015, wild mammals were lived-trapped in the tropical broadleaf moist forests of central and southern Belize. Ticks were collected from the animals and identified to species by morphological and molecular analysis (DNA sequence of the tick mitochondrial 16S RNA gene). Some of the ticks were tested for rickettsial infection by molecular methods (DNA sequences of the rickettsialgltA andompA genes). Results A total of 84 ticks were collected from 8 individual hosts, as follows:Amblyomma pacae from 3Cuniculus paca ;Amblyomma ovale andAmblyomma coelebs from aNasua narica ;A. ovale from anEira Barbara ;A. ovale, Amblyomma cf.oblongoguttatum, andIxodes affinis from aPuma concolor ; andA. ovale, A. coelebs, A . cf.oblongoguttatum, andI. affinis from twoPanthera onca . Three rickettsial agents were detected:Rickettsia amblyommii inA. pacae, Rickettsia sp. strain Atlantic rainforest inA. ovale, andRickettsia sp. endosymbiont inIxodes affinis . Conclusions The present study provides unprecedented records of ticks harboring rickettsial agents in the New World. An emerging rickettsial pathogen of South America, Rickettsia sp. strain Atlantic rainforest, is reported for the first time in Central America. Besides expanding the distribution of 3 rickettsial agents in Central America, our results highlight the possible occurrence ofRickettsia sp. strain Atlantic rainforest-caused spotted fever human cases in Belize, since its possible vector, A. ovale, is recognized as one of the most important human-biting ticks in the Neotropical region.